Interpretation Verse of Religious Moderation: Systematic Library Review Meaning of Ummatan Wasathan in Qs. 2: 143 - Muhammad Faisal Hamdani (Budapest International Research and Critics University, 2022)
This study focuses on examining the interpretation of the verse on religious moderation, related to the term wastahan ummatan in QS.Al Baqarah (2): 143. This research is important in knowing the views of commentators on the Qur'anic verse regarding religious moderation and related to the contemporary context. This research uses a qualitative traditional approach, using a literature review through a systematic review method of references (Systematic Library Research) related to the focus of this study. The data analysis technique used in this study is descriptive, interpretive and deductive analysis which is carried out in stagesfformulation, search, inspection/selection, analysis-synthesis, quality control mainstreaming, and report preparation.